Players’ perspectives on locker room culture in Icelandic football - Alexander Ágúst Mar Sigurðsson 1999- (2022)
The main goal of this study was to get the perspective of football players from the top league in Iceland on the so-called "locker room culture". Through the emergence of the #metoo movement and reports of sexual scandals connected to the Icelandic national team in 2021, locker room culture has been widely discussed although studies disagree on definitions of the term. Participants completed qualitative unstandardized interviews, then analyzed by the researcher. Findings revealed five main results. That "locker room culture" can be negative but also positive. Leaders strongly affect the culture in each team. Locker room culture has progressed fast in the last few years in a positive way. Football is a homogenous culture with women and minorities still on the fringes, but individual footballers do not conform to one stereotype. Players feel they do not have the space to share emotions that might go against the norm and are afraid of being not accepted. Changes need to be made and educating and guiding athletes can construct a more inclusive type of leaders and culture. Everybody should be supported in football, also those who experience weakness and being low at times. Keywords: football, locker room culture, toxic jock, athlete, masculinity, leadership Markmið þessarar rannsóknar var að fá sjónarhorn íslenskra knattspyrnumanna úr efstu deild á „klefamenningu“. Með tilkomu #metoo hreyfingarinnar og skýrslum um kynlífshneyksli tengd íslenska landsliðinu árið 2021 hefur klefamenning verið mikið rædd þó rannsóknir séu ekki sammála um skilgreiningar á hugtakinu. Þátttakendur luku eigindlegum óstöðluðum viðtölum sem rannsakandi greindi síðan. Niðurstöður leiddu í ljós fimm megin niðurstöður. Sú „klefamenning“ getur verið neikvæð en líka jákvæð. Leiðtogar hafa mikil áhrif á menninguna í hverju liði. Búningsklefamenning hefur þróast hratt á síðustu árum á jákvæðan hátt. Fótbolti er einsleit menning með konur og minnihlutahópa enn á jaðrinum, en einstakir knattspyrnumenn falla ...